Information disclosure to cancer patients: EORTC QLQ-INFO25 questionnaire. (June 2011) - Arraras, Juan Ignacio; Greimel, Eva; Chie, Wei-Chu; Sezer, Orhan; Bergenmar, Mia; Costantini, Anna; Young, Teresa; Kuljanic, Karin; Velikova, Galina
Information is one of the main interventions given to cancer patients. Important research into information disclosure has been conducted and major advances have been made. We present the main theoretical models used to understand the information field and describe the current situation regarding the principal factors related to information: patients'' needs, coping strategies, illness representations, cross-cultural differences, the role of the family, and strategies to enhance information giving, such as professional training and patient-targeted interventions. We highlight the need to assess patients'' characteristics and desires through questionnaires and interviews and present the European Organisation for Research and Treatment of Cancer Quality of Life Group information questionnaire (EORTC QLQ-INFO 25). This instrument evaluates the level of information patients have received in different areas of their disease, treatment and care, and evaluates qualitative aspects. Finally, we describe the key areas of the information field and discuss how these areas could change in the future.